Drug Library Screening for the Identification of Ionophores That Correct the Mistrafficking Disorder Associated with Oxalosis Kidney Disease. (August 2017) - Hou, Shurong; Madoux, Franck; Scampavia, Louis; Janovick, Jo Ann; Conn, P. Michael; Spicer, Timothy P.
Primary hyperoxaluria is the underlying cause of oxalosis and is a life-threatening autosomal recessive disease, for which treatment may require dialysis or dual liver-kidney transplantation. The most common primary hyperoxaluria type 1 (PH1) is caused by genetic mutations of a liver-specific enzyme alanine:glyoxylate aminotransferase (AGT), which results in the misrouting of AGT from the peroxisomes to the mitochondria. Pharmacoperones are small molecules with the ability to modify misfolded proteins and route them correctly within the cells, which may present an effective strategy to treat AGT misrouting in PH1 disorders. We miniaturized a cell-based high-content assay into 1536-well plate format and screened 4200 pharmacologically relevant compounds including Food and Drug Administration, European Union, and Japanese-approved drugs. This assay employs CHO cells stably expressing AGT-170, a mutant that predominantly resides in the mitochondria, where we monitor for its relocation to the peroxisomes through automated image acquisition and analysis. The miniaturized 1536-well assay yielded a Z′ averaging 0.70 ± 0.07. Three drugs were identified as potential pharmacoperones from this pilot screen, demonstrating the applicability of this assay for large-scale high-throughput screening.